Fresh start: a group-based intervention to promote physical activity among college freshman - Taylor, Mia S. (Kansas State University, 2020)
Physical activity levels tend to decline as students transition from high school to college, and freshmen college women may be particularly susceptible to physical activity barriers. It is possible that providing physical activity resources and support via text messages could assist freshmen women in increasing their physical activity levels. The primary purpose of this study was to evaluate the effects of a mobile group-based intervention for freshmen female college students on physical activity and sedentary behavior. In addition, we examined intervention effects on social support, enjoyment, and stress in this population. Freshmen females (n=30) were recruited to participate in a 9-week intervention that involved wearing a physical activity monitor for three individual weeks (week 0, week 5, and week 9) and receiving tailored weekly messages via GroupMe. Participants were randomly assigned to groups of 6-7 participants, and each group was moderated by one research assistant. GroupMe discussions were specifically formatted to provide physical activity social support, promote physical activity enjoyment, enhance knowledge about benefits of physical activity, suggest ways to decrease sedentary behavior, and increase awareness of various physical activity resources on campus, such as the recreational center. Outcomes were assessed at baseline and post-intervention. Additionally, follow-up focus group sessions were conducted during the fall semester of the participants’ sophomore year to gain further feedback about the intervention. We hypothesized that students would demonstrate increases in physical activity, enjoyment, and social support, and decreases in sedentary behavior and stress after participating in the intervention. Results revealed no significant changes in physical activity or sedentary behavior based on objective data from the activPALs. A Wilcoxon Signed-Rank Test of self-reported physical activity and sedentary behavior (International Physical Activity Questionnaire) indicated increases in self-reported sitting time from baseline to post-intervention (Z=-2.654, p<0.008). There were no significant changes in enjoyment, social support, or stress from baseline to post-intervention. A total of 10 participants attended a follow-up focus group session. Key recommendations included incorporating more face to face interaction, a change of topics within the messages to focus on more nutrition and exercise and or guided exercises, and running the intervention during the fall semester rather than the spring. Aspects of the program that participants liked the best included the feedback of activity provided by the activPAL, the idea of using GroupMe for the program, and the length of the program. Overall, results did not align with our hypotheses, but the intervention results and feedback from participants will help with intervention refinement. Future studies should continue to seek creative ways to promote physical activity in this population, with an overall purpose of sustaining physical activity habits beyond the intervention.
Keywords: Female; College; Physical activity; Sedentary behavior; Freshman; Intervention